The Relationship Husband’s Support and Exclusive Breastfeeding in the Work Area of Umbulharjo 1 Public Health Center, Yogyakarta City - Rolita Efriani; Dhesi Ari Astuti (Universitas 'Aisyiyah Yogyakarta, 2020)
In order to reduce Infant Mortality and Mortality Rate (IMR), The United Nations Childrens Fund (UNICEF) and the World Health Organization (WHO) recommend that babies only be breastfed for the first six months of life (exclusive breastfeeding). The coverage of exclusive breastfeeding in the Special Region of Yogyakarta is 73.3% and the lowest is in Yogyakarta City at 59.52%, this achievement has not reached the government's target of 80%. Umbulharjo I Public Health Center is the health center with the lowest exclusive breastfeeding coverage in Yogyakarta City at 39.15%. Exclusive breastfeeding can be assessed for effectiveness from the Health Technology Assessment (HTA) aspect. This study aims to determine the relationship of husband's support with exclusive breastfeeding at Umbulharjo I Public Health Center, Yogyakarta City. This research is an analytical survey with a cross sectional approach. Samples of 64 mothers were taken from a population of 179 mothers who had 6-12 months old infants. Data were analyzed by Chi-Square test. The results of the analysis of the husband's supportwith exclusive breastfeeding obtained a p-value of 0.019 (p 0.05). Conclusion, there is a relationship between husband's support and exclusive breastfeeding in the working area of the Umbulharjo I Public Health Center.